Consumer satisfaction-oriented emotional marketing in foreign trade - Zhu, Lei; Gao, Yanhua; Chen, Weijing; Ren, Hao (Frontiers in Psychology, 2022)
This research uses an experimental approach to investigate the relationship between a company's market orientation and its level of success in international business. It was decided to develop and use a market orientation scale that was appropriate to the sector. It was discovered that there are four hidden traits that drive market orientation. These include customers, rivals, departmental response, and overall customer satisfaction. According to the results, an orientation toward one's customers is more essential than any of the other traits, while an orientation toward one's competitors has an inverted U-shaped connection with performance. The performance of the firm was not found to correlate in any way with the responsiveness of its departments. With the help of the comprehensive conceptualization, managers are able to develop specific kinds of orientations that are essential for higher levels of performance.